Light and scanning electron microscopic observation of palynological characteristics in spineless Astragalus L. (Fabaceae) and its taxonomic significance. Issue 7 (18th March 2022) - Khan, Amjad; Ahmad, Mushtaq; Zafar, Sadia; Abbas, Qamar; Arfan, Muhammad; Zafar, Muhammad; Sultana, Shazia; Ullah, Sher Aman; Khan, Siraj; Akhtar, Anam; Kilic, Omer; Ozdemir, Fethi Ahmet
Abstract: Palynological characterization is considered to be one of the significant taxonomic tools for the delimitation and identification of morphologically complicated taxa. Hence, the pollen morphology of 12 species of spineless Astragalus L. was examined using light and scanning electron microscopy. Studied pollen were small to medium, monad, prolate to per‐prolate and tricolporate type in all studied taxa. The exine sculpturing varied from reticulate to microreticulate whereas colpus ornamentation ranged from scabrate to granulate. Furthermore, maximum polar and equatorial diameter was recorded in Astragalus leucocephalus Bunge. (45.00 μm) and A. pyrrhotrichus Boiss. (22.91 μm) while minimum in A. amherstianus Benth. ex Royle (28.75 μm) and A. amherstianus Benth. ex Royle (15.00 μm), respectively. Similarly, the ratio of polar to equatorial diameter was recorded maximum in A. ophiocarpus Boiss. (2.05). The width of colpi was larger in A. hamosus L. (1.29 μm) and smaller in A. ophiocarpus Boiss. (0.62 μm). We have also found the maximum value of mesocolpium in A. retamocarpus Boiss. (2.08 μm) while minimum in A. oxyglottis Steven ex M.Bieb. (1.87 μm). The quantitative pollen attributes helped in the development of pollen keys for the accurate and quick identification of the studied species. Furthermore, ordination and cluster analysis were performed for the differentiation of the investigated taxa at species level. Based on our results, we conclude that pollen features can be used for the delimitation and identification of the studied taxa. Research Highlights: Pollen micromorphology is a useful tool for classifying complicated taxa. The pollen micromorphology of 12 spineless species of Astragalus L. was studied using LM and SEM. The observed pollen characteristics aided in Astragalus L. serve for the identification and classification of taxa at specific level. Abstract : Beief sketch of palynological study on Spineless Astragalus L.